2021
DOI: 10.3390/genes12121938
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Genetic Variants Revealed from a Rat Model of Brain Ischemia in Patients with Ischemic Stroke: A Pilot Study

Abstract: Although there has been great progress in understanding the genetic bases of ischemic stroke (IS), many of its aspects remain underexplored. These include the genetics of outcomes, as well as problems with the identification of real causative loci and their functional annotations. Therefore, analysis of the results obtained from animal models of brain ischemia could be helpful. We have developed a bioinformatic approach exploring single nucleotide polymorphisms (SNPs) in human orthologues of rat genes expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The patients with low scores are then compared to those with high scores [ 7 , 20 ]. Because there is no consensus regarding optimal grouping, we also applied directional ∆mRS, as recently proposed by ourselves [ 19 ]. We also divided the patients into three groups using mRS. With regard to the latest variant, we considered the specific characteristics of all the patients with an mRS score of 3 (see Section 4 for details).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients with low scores are then compared to those with high scores [ 7 , 20 ]. Because there is no consensus regarding optimal grouping, we also applied directional ∆mRS, as recently proposed by ourselves [ 19 ]. We also divided the patients into three groups using mRS. With regard to the latest variant, we considered the specific characteristics of all the patients with an mRS score of 3 (see Section 4 for details).…”
Section: Discussionmentioning
confidence: 99%
“…The selected tag SNPs were genotyped with the use of self-designed TaqMan real-time PCR assays. The name of the software used, as well as the description of the components of the PCR reaction mixture and the general cycling conditions, was the same as described in our previous study [ 19 ]. The sequences of the primers and probes used in the current study are presented in Table 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the authors had developed a bioinformatic approach to exploring single-nucleotide polymorphisms (SNPs) in human orthologues of rat genes expressed differentially under conditions of induced brain ischemia [ 6 ]. Using this approach, the authors identified and analyzed nine SNPs in 553 Russian individuals (331 patients with IS and 222 controls) [ 7 ]. Moreover, Khrunin et al explored the association of SNPs with both IS outcomes and the risk of IS.…”
mentioning
confidence: 99%
“…SNPs rs62278647 and rs2316710 (PTX3) were associated significantly with IS ( p = 0.000029 and p = 0.0025, respectively). These correlations for rs62278647 and rs2316710 were found only in women, which suggests a sex-specific association of the PTX3 polymorphism [ 7 ]. Thus, the research of Khrunin et al does not only reveals some new genetic associations with IS and its outcomes but also shows how exploring variations in genes from a rat model of brain ischemia can be of use in searching for human genetic markers of this disorder [ 7 ].…”
mentioning
confidence: 99%